APPLICATION OF LINEAR PROGRAMMING TO MINIMIZE PRODUCTION COSTS IN SMALL AND MEDIUM SCALE CASHEW CHIPS ENTERPRISE - Wiki Sabardi (Fakultas Teknik Universitas Samudra, 2023)
Consumer demand continues to increase in the food industry, especially snacks, making companies must be able to meet market needs. Companies use various methods to ensure that the quality of their products meets consumer expectations and desires. UD Keripik Mustika is a chip company made from cassava and was founded in 2006. Keripik Mustika faces the problem of optimizing production costs. The purpose of this research is to find the optimal price in the production costs of cassava chips. The method used is Linear Programming. The results obtained in this study after using the POM-QM software were a total production cost of Rp. 252,670,000, the total inventory cost is Rp. 1,200,000, and a total Production Cost of Rp. 253,870,000.